Toward an integrated paradigm of Islamic knowledge classification: Reconstructing Al-Farabi and Al-Ghazali for contemporary Islamic scholarship - Faza Firdaus; Khaerudin (PT Perfidia Akademia, 2026)
The classification of knowledge in the Islamic intellectual tradition has been widely examined; however, most studies remain limited to comparing classificatory structures rather than reconstructing the philosophical paradigm underlying the Islamic knowledge system. This study aims to reconstruct the paradigm of knowledge classification through a philosophical comparative analysis of Al-Farabi and Al-Ghazali to formulate a conceptual framework for the development of the contemporary Islamic knowledge system. The research employs a qualitative library-based approach using philosophical comparative analysis through the stages of identification, comparison, interpretation, and reconstruction. The findings reveal that Al-Farabi conceptualizes knowledge classification as an architecture of knowledge, whereas Al-Ghazali frames it as a legitimation of knowledge, indicating a complementary rather than oppositional relationship. Based on this synthesis, the study proposes the Integrated Paradigm of Islamic Knowledge Classification, which integrates ontological, epistemological, axiological, and contemporary dimensions as a conceptual contribution to the development of a more integrative Islamic knowledge system. Abstrak Klasifikasi ilmu dalam tradisi intelektual Islam telah banyak dikaji, namun sebagian besar penelitian masih berfokus pada perbandingan struktur klasifikasi sehingga belum merekonstruksi paradigma filosofis yang melandasi sistem keilmuan Islam. Penelitian ini bertujuan merekonstruksi paradigma klasifikasi ilmu melalui analisis komparatif filosofis terhadap pemikiran Al-Farabi dan Al-Ghazali guna merumuskan kerangka konseptual bagi pengembangan sistem keilmuan Islam kontemporer. Penelitian menggunakan pendekatan kualitatif berbasis kepustakaan dengan analisis komparatif filosofis melalui tahapan identifikasi, komparasi, interpretasi, dan rekonstruksi. Hasil penelitian menunjukkan bahwa Al-Farabi membangun klasifikasi ilmu sebagai architecture of knowledge, sedangkan Al-Ghazali memosisikannya sebagai legitimation of knowledge, sehingga keduanya bersifat komplementer, bukan oposisional. Berdasarkan sintesis tersebut, penelitian ini menghasilkan Integrated Paradigm of Islamic Knowledge Classification yang mengintegrasikan dimensi ontologis, epistemologis, aksiologis, dan implikasi kontemporer sebagai kontribusi konseptual bagi pengembangan sistem keilmuan Islam yang lebih integratif.